Theologia Moralis: Tomus I. - B. T. G. (America Magazine: The Jesuit Review of Faith & Culture, 1923)
The article reviews the book "Theologia Moralis: Tomus I. Theologia Fundamentalis," by Arthurus Vermeersch.